1975
DOI: 10.1530/jrf.0.0440011
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Oestrogen Administered During the Progestational Phase of the Cycle on Transport of Spermatozoa in Ewes

Abstract: Summary. Two split-plot factorial experiments are described, the first with 72 entire cyclic ewes and the second with 80. The pattern of transport of spermatozoa through the reproductive tract was studied, following treatments with progestagen and oestrogen or with oestrogen alone during 2 weeks preceding insemination. A daily dose of 25 \ g=m\ g oestradiol-17\g=b\ administered to ewes for 14 days preceding oestrus had a deleterious effect on the passage of spermatozoa through the cervix into the uterus within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

1978
1978
1987
1987

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…This time-scale is even more rapid than has been previously inferred from reports of significant numbers of spermatozoa being recovered from the cervix at varying times from 15 min to 2 h after insemination (e.g. Mattner 1963a; Quinlivan and Robinson 1969;Lang and Oh 1970;Lightfoot and Salamon 1970;Hawk and Conley 1975;Croker et al 1975). Also, Quinlivan and Robinson (1967) claimed that cervical reservoirs are established within 1 h of insemination.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…This time-scale is even more rapid than has been previously inferred from reports of significant numbers of spermatozoa being recovered from the cervix at varying times from 15 min to 2 h after insemination (e.g. Mattner 1963a; Quinlivan and Robinson 1969;Lang and Oh 1970;Lightfoot and Salamon 1970;Hawk and Conley 1975;Croker et al 1975). Also, Quinlivan and Robinson (1967) claimed that cervical reservoirs are established within 1 h of insemination.…”
Section: Discussionmentioning
confidence: 77%
“…Such rapid entry of spermatozoa into the cervix of the oestrous ewe would be advantageous because within the cervix spermatozoa are well protected (Robinson 1973) and retain their motility longer than in other parts of the tract (Quinlan et al 1933). The numbers of spermatozoa in the cervix 2 h after insemination are correlated with numbers in the oviducts at 22 h (Hawk and Conley 1975) and 24 h (Croker et al 1975) after insemination which emphasizes the importance of the early transport of spermatozoa into the cervix soon after insemination. Croker et al (1975) compared their key data to those of Robinson (1973) and concluded that the patterns of fertility were established within 2 h of insemination.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations